Improvement of Methods for Improving the Effectiveness of Fire-Rescuers ' Mental Training - Тurdiev Sardor Utkir ugli (Research Parks Publishing LLC, 2022)
Today, in 193 countries around the world, 7-8 million fires occuтevery year, resulting in the loss of 85-90 thousand people, while the volume of material damage is billions of US dollars. Based on these statistics, there is a sharp increase in the number of fires. The increase in the number of such fires has a serious impact on material damage and the environmental environment. In order to prevent fires that may occur, to ensure a quick and easy shutdown, there are still studies on increasing the effectiveness of the organization of emergency rescue work, as well as on the provision of technical means. In particular, the use of innovative methods in eliminating emergency situations, fire extinguishing is required to increase the effectiveness of fire extinguishing by improving technical means and methods. At the same time, the development of new categories of fire extinguishing technical means, further improvement of their effectiveness is required.